TRANSLATION OF ENGLISH HEALTH AND MEDICAL IDIOMS INTO VIETNAMESE: A STUDY BASED ON ESP MATERIALS AT A UNIVERSITY OF NURSING / Vũ Thị Thu Phương; NHDKH Dr Tran Thi Thu Hien - Vũ, Thị Thu Phương
As the title indicates the study aims at studying the translation of English health and medical idioms made by nursing students at a university of nursing. The study is aimed at two point: (1) the procedures and strategies are used by nursing students in translating English health and medical idioms into Vietnamese and (2) the common errors made by nursing students in translating English health and medical idioms into Vietnamese. This study emplpyed quantitative method by analyzing data collected from translation tasks assigned for nursing students and in-depth interview. According to the data analysis, the findings of the study show that the students only applied some procedures and strategies instructed in the first week of ESP module and they made common errors of translating health and medical idioms in ESP materials. The study not only supplies some implications to language teaching, learning as well as translating but also raises language users’ awareness of English health and medical idioms so that they can use them exactly and be successful in their real life communication in English